Antonio Gramsci: política y teoría en la cultura argentina del siglo XXI - Cortés, Martín; Gómez, Sebastián (International Gramsci Journal, 2023)
This is the abstract of the Spanish-language article by Martín Cortés and Sebastián Gómez on the current situation of Gramsci studies in Argentina.